2013
DOI: 10.1016/j.ijsu.2013.03.013
|View full text |Cite
|
Sign up to set email alerts
|

Modified radical mastectomy: A pilot clinical trial comparing the use of conventional electric scalpel and harmonic scalpel

Abstract: HSs do not decrease the seroma rate. However, this method may be useful in skin sparing mastectomy because it decreases skin flap necrosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
20
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 24 publications
4
20
1
Order By: Relevance
“…Similar results have been shown in studies by Kozomara et al .,[21] Ribeiro et al .,[24] and Rohaizak et al . [17] Infection was more common in patients who developed seroma, hematoma, or flap necrosis.…”
Section: Discussionsupporting
confidence: 92%
“…Similar results have been shown in studies by Kozomara et al .,[21] Ribeiro et al .,[24] and Rohaizak et al . [17] Infection was more common in patients who developed seroma, hematoma, or flap necrosis.…”
Section: Discussionsupporting
confidence: 92%
“…In our study, mean drain output in electrocautery group was 471.3ml and 387.1ml in ultrasonic shear group. Except for the results reported by Ribeiro GH et al, 3 the mean drain output in our study was lesser than the studies done by Deo S et al, 5 Rohaizak Met al 11 and Mittal et al 6 The mean drain output in our study in the electrocautery patients was higher than the electrocautery group. This is statistically significant (P <0.0001).…”
Section: Discussioncontrasting
confidence: 87%
“…In our study, mean blood loss in electrocautery group was 417.1ml and 370.0ml in ultrasonic shear group. Except for the results reported by Ribeiro GH et al, 3 the mean blood loss in the harmonic group has been indicated to be significantly less as compared to the electrocautery group.…”
Section: Discussionmentioning
confidence: 68%
See 2 more Smart Citations